ZnO nanoparticles dispersed PVA–PVP blend matrix based high performance flexible nanodielectrics for multifunctional microelectronic devices - Choudhary, Shobhna; Sengwa, R.J. (Current applied physics, 2018)
Polymer nanocomposite (PNC) films based on the blend matrix of poly(vinyl alcohol) (PVA) and poly(vinyl pyrrolidone) (PVP) (50/50 wt%) incorporated with zinc oxide (ZnO) nanoparticles (i.e., (PVA–PVP)–x wt% ZnO; x = 0, 1, 3 and 5) were prepared by solution-cast method. The behaviour of polymer-polymer and polymer-nanoparticle interactions in the PNC films was ascertained by employing X-ray diffraction, energy dispersive X-ray, and Fourier transform infra-red spectroscopies. Scanning electron microscopy and atomic force microscopy were performed for the morphological characterization, whereas the thermal and optical properties of the PNC films were investigated by using differential scanning calorimetry and ultraviolet–visible spectroscopy, respectively. The dielectric and electrical behaviour of these PNC materials were determined by employing the dielectric relaxation spectroscopy over the frequency range from 20 Hz to 1 MHz. The influence of ZnO concentration on the degree of PVA crystalline phase and the crystallite size, surface morphology and roughness of the films, the glass phase transition and melting phase transition temperatures, direct and indirect optical energy band gap, refractive index, complex permittivity, electrical conductivity, activation energy and the structural dynamics of these PNC materials were explored. The investigated properties of the PNC films were credited to an innovation and engineering of novel high performance flexible nanodielectrics in the area of advanced functional materials for their promising applications especially in the next generation optoelectronic, gas sensor and microelectronic devices. [Display omitted] •Multifunctional (PVA–PVP)–x wt% ZnO films were prepared by solution-cast method.•Polymer-polymer and polymer-nanofiller interactions vary with ZnO concentration.•Optical band gap decrease with the increase of ZnO contents in the PNC films.•Only 1 wt% ZnO dispersion enhances permittivity and thermal stability of PNC film.•Uses as nanodielectric, sensor and base matrix for electrolyte were established.